A journey along the TIM23 complex, the major protein translocase of the mitochondrial inner membrane - Günsel, Umut; Mokranjac, Dejana (Biologia Serbica, 2020)
Proper structure and function of mitochondria depends on translocation of over a thousand different mitochondrial proteins from the cytosol. Mitochondrial proteins carry a number of different targeting signals and are translocated into the mitochondria by a number of different protein translocases. Here, we provide an overview of mitochondrial protein translocation pathways, and focus on the TIM23 complex, the major protein translocase of the mitochondrial inner membrane.